TINJAUAN YURIDIS HAK REHABILITASI PADA KORBAN PENYALAHGUNAAN NARKOTIKA (KAJIAN UNDANG-UNDANG NOMOR 35 TAHUN 2009) - Ramadhana, Widodo; Farhansyah, Reza; Khairunnisa Nasution, Dinda; Christofel Sinaga, Mathew (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to examine the implementation of rehabilitation rights for victims of drug abuse within the framework of Indonesian law, based on Law Number 35 of 2009 concerning Narcotics. This study focuses on the role of government institutions, such as the Indonesian National Police (Polri), the National Narcotics Agency (BNN), the Ministry of Law and Human Rights (Kemenkumham), the Prosecutor's Office, and the Supreme Court in the rehabilitation process. The research method used is normative research with a case study approach, which relies on the analysis of legal documents, including laws, regulations, and relevant court decisions. The results of the study indicate that although Law Number 35 of 2009 has regulated the right to rehabilitation for victims of drug abuse, its implementation is still limited. This is due to the lack of understanding of the community and law enforcement officers regarding the rehabilitation process that has been established. Therefore, further efforts are needed to increase awareness and coordination between related institutions in ensuring that rehabilitation rights can be accessed by all victims of drug abuse. This study concludes that more effective legal policies and synergy between government institutions are needed to improve the welfare of drug victims in Indonesia.